PERBANDINGAN KADAR KALSIUM (Ca) DAN FOSFOR (P) ANTARA SAPI PERANAKAN ONGOLE DAN SIMMENTAL PO DAN HUBUNGANNYA DENGAN SERVICE PER CONCEPTION - , F. WINANT FEBRIARNO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Calcium ( Ca ) and Phosphorus ( P ) is a macro mineral that is essential for the heifers and adult cattle. The function of Ca and P in the body not only play a role in the formation of bones and teeth structure but also have an effect on reproductive performance. This study aimed to compare the levels of Ca and P between PO and SimPO and its relationship with the service per conception (S/C). This study uses nine PO and seven SimPO cattle aged between two until five years, clinically healthy, and ever give birth at least once. Blood samples were taken from each cow to determine levels of Ca and P in the serum . This study was also performed by the method of survey and interviews to farmers to determine reproductive performance, specifically the S/C. Data were analyzed using independent t - test. The results showed that serum concentration of PO cattle had an average of Ca and P, respectively for 9,09 ± 0,86 mg/dl and 7,30 ± 1,39 mg / dl, while concentration of Ca and P levels in the serum of SimPO cattle amounted to 10,14 ± 0,91 and 5,61 ± 0,58 mg/dl. The results of the analysis using independent t - test showed significant difference (P<0,05) levels of Ca and P between PO and SimPO cattle. In the analysis of the results of S/C was 2,00 ± 1,12 on PO and 1,71 ± 1,11 on SimPO, which is based on the results of independent t - test there was no significant difference (P>0,05) between PO and Simpo. Based on the analysis of Ca and P levels in the PO and Simpo cattle is normal, so were the results of the S/C which showed normal results thus it can be concluded that in this study the levels of Ca and P in PO and Simpo cattle does not affect the S/C.